A retrospective study to assess the complications associated with surgical management of distal radius fracture by ligamentotaxis - S., Sachindhar; Sarvotham, Ananya; S., Sujai (International Journal of Research in Orthopaedics, 2024)
Background: Fractures of the distal radius are the most common upper limb fractures encountered by orthopedic surgeons. It constitutes about 75% of all the forearm fractures. There is steady increase in this type of fracture in all age groups but is the highest in children and elderly. There are multiple modalities of treatment available for distal end radius fractures, among which ligamentotaxis is one of the modalities, where the ligaments, retinaculum, tendons and periosteum that envelope the fracture serves as barrier during open reduction, helps achieve the reduction of the fracture. The objective is to study the most common complication associated with distal radius fractures treated by ligamentotaxis in this institution. Methods: This hospital based retrospective study was conducted at MVJMC and RH after receiving ethical clearance from the institutional ethical committee. The study population contained 50 patients that met the inclusion criteria over a period of 4 years from March 2019 to March 2024.The administrative health data was collected from OPD and OT registers, and the collected data was entered in Microsoft excel and results were calculated and tabulated at the end of the period. All the patients with distal end radius fractures treated by ligamentotaxis over a period of 4 years were included Results: According to the study distal end radius fracture was more prevalent among males than females and the highest percentage with 30% was seen among the age group of 31-40 years. The most common complication encountered was neuropathy and residual wrist pain which accounted for 14%. Conclusions: The study concludes that most of the fractures and its complications are note among the active age group. The study helps understand the complications and find strategies to reduce the complication percentage.